Ferroelectric Ceramic Materials Prepared by Nanoparticles in Outdoor Environmental Sculpture Art - Ning Zhang; Jiexu Li; Ying Xia (Advances in Materials Science and Engineering)
With the development and progress of the city, people’s research on outdoor sculpture has gone deeper, and the field of material research has been raised to the field of spiritual culture. Tang Sancai is beautiful in color and wonderful in shape, such that when ceramics are used in outdoor environmental sculpture art, except for its performance, its appearance and tone must also be taken into consideration. Even when ferroelectric ceramics are used in outdoor sculptures, changing their shapes and taking into account their colors can be done invisibly only by passing through an electromagnetic field. Ferroelectric ceramics are generally divided into insulating, dielectric, piezoelectric, magnetic, semiconductor, transparent, and infrared sensor ceramics. This article integrates the manufacturing method of ferroelectric ceramics into outdoor environmental sculpture art. First of all, this article describes the ferroelectric ceramics and outdoor environmental sculptures, explains the method of preparing ferroelectric ceramics from barium titanate nanoparticles, and explains the pyroelectric inverse process of the electric card effect principle of electric ceramic materials, the thermodynamics of Maxwell’s relationship, and the thermodynamics of Landau’s phenomenological theory. The elasticity of the system is calculated, and the preparation of tetragonal barium titanate ferroelectric ceramics prepared by hydrothermal nanoparticles and SBT/Cu ferroelectric ceramic composites prepared by nanoparticle metallurgy is explained. In the plasma discharge mode, the optimal temperature for sintering the composite material is obtained. Then through experiments, research on the preparation and performance of the high dielectric constant BTnf-Ag/PVDF ferroelectric ceramic nanocomposite and its application in environmental sculptures are demonstrated. Compared with the two ancient BTnf/PVDF composite materials, the barium titanate fiber prepared by electrostatic spinning shows that the BTnf-Ag/PVDF composite material has a higher dielectric constant, and the dielectric loss is not too high. The 41.8vol% BTnf-Ag composite material has a dielectric constant of 82.6BTnf/PVDF, but the composite material’s dielectric constant is only 62.4, an increase of 32%. The dielectric loss of the 41.8vol% BTnf-Ag composite material is 0.053, and the dielectric loss constant of the BTnf/PVDF composite material is 0.049; the dielectric loss is reduced by 8% year-on-year. Ferroelectric ceramic composites prepared by adding silver ions have ideal dielectric properties and enhanced energy storage density.